Impact of exchange rate fluctuations on trade in Nigeria: an empirical analysis (1990-2023) - Adeniji, Kehinde Adegoke (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2023)
The study examined time series analysis from 1990 - 2023 to examine exchange rate fluctuations on trade in Nigeria. Autoregressive distribution lag model (ARDL) for testing the short-run and long-run relationship between trade and exchange rate fluctuation in Nigeria. Results of the empirical revealed, that exchange rate fluctuation affects GDP either in the short run or in the long run. Excessive exchange rate fluctuation affects economic growth in Nigeria. The study recommends that the government needs to reduce wasteful spending on unproductive expenditures with little or no return to the economy. Awareness should be in encouraging citizens to patronize local produce; the action leads the country's currency to appreciate against foreign currency.